ADMINISTRATIVE REFORM AND THE AGENCY MODEL OF PUBLIC ADMINISTRATION - Dejan Vučinić
Administrative reform in various countries is conditioned by various social, political, and economic factors. In this regard, we cannot talk about the same reasons for reform for every country. However, what is common to all cases is the crisis of state governance and the need to transform the existing system, reduce state interventionism, and increase efficiency and productivity. The terms “efficiency” and “productivity”, in the context of the state and its administrative system, take on a different quality and somewhat altered meaning compared to their usual context, as they are shaped by their connection to the public interest. The reforms implemented in the former socialist countries, however, have a different background. They are partly the result of aspirations for rapid economic progress and partly the outcome of mandatory changes required by the European Union. Without deciding which of these reasons prevail, the author will discuss the reasons that brought about the need for new models of public administration. These models aim to overcome the crisis of state governance, focusing particularly on the agency model of public administration, which, as a trend, has been widely adopted in many countries. This model of public administration has also been extensively applied in the case of administrative reform in the Republic of Serbia. Considering their role and prevalence, it can be said that this represents a unique model of public administration reform.This model of public administration has been commonly applied in the case of administrative reform in the Republic of Serbia. Considering their role and number, we can say that it is an authentic model of public administration reform.